The Discovery of Blue-cored Dwarf Early-type Galaxies in Isolated Environments - Soo-Chang Rey; Suk Kim; Jiwon Chung; Youngdae Lee (The Astrophysical Journal, 2023)
The presence of blue-cored dwarf early-type galaxies (dE(bc)s) in high-density environments supports the scenario of the transformation of infalling late-type galaxies into quiescent dwarf early-type galaxies by environmental effects. While low-density environments lacking environmental processes could not be relevant to the formation of dE(bc)s, we discovered a large sample of rare dE(bc)s in isolated environments at z < 0.01 using the NASA–Sloan Atlas catalog. Thirty-two isolated dE(bc)s were identified by visual inspection of the Sloan Digital Sky Survey images and g − r color profiles. We found that (1) isolated dE(bc)s exhibit similar structural parameters to dE(bc)s in the Virgo cluster; (2) based on the color–magnitude relation, color gradients, and optical emission lines of dE(bc)s, isolated dE(bc)s show more vigorous, centrally concentrated star formation (SF) compared to their counterparts in the Virgo cluster; (3) at a given stellar mass, isolated dE(bc)s tend to have a larger fraction of gas mass than their Virgo counterparts. We discuss a scenario of episodic SF sustained by gas accretion, suggested by Sánchez Almeida et al., in which the star-bursting blue compact dwarf galaxy (BCD)−quiescent BCD (QBCD) cycle can be repeated during the Hubble time. We suggest that, in this cadence, isolated dE(bc)s might be QBCDs at pre- or post-BCD stages. Our results imply that dE(bc)s comprise a mixture of objects with two types of origins, nature or nurture, depending on their environment.